Assessment of Risk of Possible Exposure to Rabies among Processors and Consumers of Dog Meat in Zaria and Kafanchan, Kaduna State, Nigeria - Odeh, Leslie E. (Glob J Health Sci, 2014)
Canine rabies is endemic in Nigeria. Some of the dogs slaughtered for human consumption may be infected with rabies virus, thus exposing handlers of raw dog meat to the disease since the virus may be present in the nerves in the meat. A cross-sectional study was designed and a structured questionnaire was designed and administered to a convenience sample of 160 processors and consumers (100 from Zaria and 60 from Kafanchan), by face to face interview at the slaughter sites or dog meat sale points. The questionnaire sought information on demographic characteristics of the respondents, rabies knowledge, attitude and actions the respondents would take if exposure occurs. Associations between demographic variables and categorized knowledge, attitude or practice scores were assessed using χ(2) analysis. The relationship between non-categorized scores was assessed using multiple regression analysis. Also, 154 brain samples from slaughtered dogs (74 from Zaria and 80 from Kafanchan) were checked for rabies antigen using direct fluorescent antibody test. Of the 160 respondents, 49 (30.6%) were involved in the slaughtering and sale of dog meat while 111(69.4%) were involved in handling and consumption of processed dog meat. Only 123(76.9%) knew that dogs are common source of rabies in Nigeria and 105(65.6%) knew that rabies affect humans. Also 110(68.8%) did not have adequate knowledge of the clinical signs of rabies. The level of knowledge, having positive attitudes and knowing acceptable practices were directly proportional to the level of education. Respondents from Kafanchan had higher level of knowledge and more positive attitudes towards rabies than those from Zaria. There were significant correlations between knowledge and attitude scores (r=0.49) and between knowledge and practice scores (r=0.43) at p<0.001. Rabies antigen was detected in the brain of 6 (3.9%) of the slaughtered dogs. The findings indicate that processors and consumers of dog meat are deficient in the knowledge of rabies. There is therefore a need for educational programmes targeted at this high risk group to increase their level of knowledge and reduce the risk of exposure.